Quercetin promotes production of secondary hair follicle stem cells in cashmere goat: a mechanistic study - Lian, Wei; Jiang, Guoqing; Wu, Xueyong; Gao, Yadong; Cui, Kun; Zhu, Lei; Xu, Ziyang; Zhang, Xiao; Wang, Jiawei; Peng, Mingli; Ding, Rui; Hao, Fei; et al. (Frontiers in Veterinary Science, 2025)
IntroductionThis study investigated the effects of quercetin on the proliferation and apoptosis of secondary hair follicle stem cells (SHFSCs) isolated from Arbas cashmere goats.MethodsSHFSCs were treated with varying quercetin concentrations. CCK-8, EdU assays, and flow cytometry analyses were performed to assess cell proliferation and apoptosis. Transcriptome analyses were used to identify differentially expressed genes and enriched signaling pathways.ResultsTreatment with 10 μg/mL quercetin for 48 h significantly promoted cell proliferation. The proportion of S-phase cells increased from 15.5% to 21.2%, and the mRNA and protein levels of PCNA and TERT were upregulated. Quercetin inhibited apoptosis by downregulating BAX, TP53, and CASP3, upregulating BCL2, and reducing the number of late apoptotic cells. Mechanistically, quercetin activated the PI3K–Akt, Wnt, and TGF-β signaling pathways, upregulated CCND1 and CDK4 expression, improved mitochondrial membrane potential, reduced ROS levels, and promoted VEGF, FGF, and HGF secretion. Transcriptome analyses revealed that differentially expressed genes were enriched in translational processes, insulin-like growth factor binding, and proliferation-related signaling pathways.ConclusionQuercetin promotes SHFSC proliferation and inhibits apoptosis through multiple pathways, providing a potential regulatory strategy for improving cashmere production in goats.